Analisis Nilai Edukatif dalam Cerita “Laowõmaru” Karya Sukawati Zalukhu - Norma Desta Lenta Waruwu; Noveri Amal Jaya Harefa (Indo-MathEdu Intellectuals Journal, 2023)
Literature is the creation of a person from the thoughts and feelings they have. Through literature, authors try to express the ups and downs of people's lives that they feel or experience. One part of literature is short stories. Short stories are literary works in which the author reflects on nature and human life.  However, in this case, the educational value contained in several values, one of which is religious value, which today is not uncommon to see many students who have begun to abandon religious values, which in this case are the pride of parents and others. The storybook Laowömaru by Sukawati Zalukhu contains educational values that exist in the lives of Nias people.  The purpose of this research is to find out the educational values contained in the story of Laowömaru by Sukawati Zalukhu and can be used as a lesson to be applied in everyday life, especially educational values: religious, aesthetic, social, moral, and cultural. The method used in this research is qualitative research method by processing secondary data. Based on the results of the study, the conclusion is that 5 educational values were found, namely (1) religious values, (2) aesthetic values, (3) social values, (4) moral values, (5) culture.